Poor hand hygiene by college students linked to more occurrences of infectious diseases, medical visits, and absence from classes - Prater, Kayla J.; Fortuna, Crystal A.; McGill, Janis L.; Brandeberry, Macey S.; Stone, Abigail R.; Lu, Xu (American journal of infection control, 2016)
Proper hand hygiene has been linked to lower susceptibility to infectious diseases in many types of communities, but it has not been well established on college campuses. This study investigated the hand hygiene statuses of college students and their occurrences in relation to infectious diseases, medical visits, and absence from classes or work. It also examined the effects of education on handwashing technique to improve hand hygiene. College students enrolled at a university in Northwestern Ohio were recruited as study subjects. Microbial samples were collected 3 times from each of the 220 valid volunteers before washing their hands, after washing with their own procedures, and after washing with a procedure recommended by the Centers for Disease Control and Prevention (CDC). Each volunteer also answered a survey including questions on their health conditions, medical visits, and absence from classes or work. Hands of 57.7% volunteers were colonized by an uncountable number of microbial colonies, which were significantly linked to more occurrences to infectious diseases (P < .05), medical visits (P < .05), and arguably more absence from classes or work (P = .09). The handwashing procedure provided by the CDC significantly improved hand hygiene. It is critical to promote education on proper handwashing in colleges, in grade schools, and at home to improve health and learning outcomes.